2022
DOI: 10.23887/jisd.v6i2.45127
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Google Classroom Usage on Student’s Learning Outcomes for Elementary School Students

Abstract: The Covid-19 pandemic has caused various changes in the education system in Indonesia, especially in the use of online learning methods. However, implementing new technologies is challenging, especially for parents and teachers of lower-grade elementary school students. One form of technology that is applied in online learning is Google Classroom. This study aims to analyze the relationship between using Google Classroom during the Covid-19 pandemic and its effect on the learning process and outcomes. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Some online platforms are usually used in online learning, such as Zoom, email, Telegram, Google Meet, and Google Classroom (Ro'fah et al, 2020). A study related to the use of Google Classroom in learning shows that it is useful in saving time, overcoming living distance, and saving learning documents (Divariyani & Slameto, 2022;Gaba et al, 2021). It also reveals that students involved in the study found Google Classroom much more straightforward and friendlier than other online platforms to use in the teaching and learning process (Ketut Sudarsana et al, 2019;Salam, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Some online platforms are usually used in online learning, such as Zoom, email, Telegram, Google Meet, and Google Classroom (Ro'fah et al, 2020). A study related to the use of Google Classroom in learning shows that it is useful in saving time, overcoming living distance, and saving learning documents (Divariyani & Slameto, 2022;Gaba et al, 2021). It also reveals that students involved in the study found Google Classroom much more straightforward and friendlier than other online platforms to use in the teaching and learning process (Ketut Sudarsana et al, 2019;Salam, 2020).…”
Section: Introductionmentioning
confidence: 99%